2023
DOI: 10.1038/s41467-023-38869-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural mapping of PEAK pseudokinase interactions identifies 14-3-3 as a molecular switch for PEAK3 signaling

Abstract: PEAK pseudokinases regulate cell migration, invasion and proliferation by recruiting key signaling proteins to the cytoskeleton. Despite lacking catalytic activity, alteration in their expression level is associated with several aggressive cancers. Here, we elucidate the molecular details of key PEAK signaling interactions with the adapter proteins CrkII and Grb2 and the scaffold protein 14-3-3. Our findings rationalize why the dimerization of PEAK proteins has a crucial function in signal transduction and pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…Here, like Grb2, they were identified as interactors of the PEAK1 homodimer and PEAK1/PEAK2 heterodimer, with another PP1 family member, PPP1CB, associating with the PEAK1 homodimer. Of interest given a recent paper reporting a key regulatory role for 14-3-3 proteins in regulating PEAK3 effector recruitment and biological activity 24 , multiple 14-3-3 isoforms bound both homodimers and the heterodimer (Supp. Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, like Grb2, they were identified as interactors of the PEAK1 homodimer and PEAK1/PEAK2 heterodimer, with another PP1 family member, PPP1CB, associating with the PEAK1 homodimer. Of interest given a recent paper reporting a key regulatory role for 14-3-3 proteins in regulating PEAK3 effector recruitment and biological activity 24 , multiple 14-3-3 isoforms bound both homodimers and the heterodimer (Supp. Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We utilized this approach since it more selectively addresses the impact of CAMK2-mediated PEAK1 phosphorylation, while RA306 treatment would exert a more general inhibition of CAMK2-mediated cellular phosphorylation. Binding of the adaptors Crk-L and Grb2, which associate with PEAK1 via SH3 and SH2 domain-mediated interactions, respectively 9,24 , was unaffected by the CIM mutations (Supp. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pseudokinases PEAK1/3 are important scaffolding regulators for the EGFR signalling ( Paul et al, 2022 ). A recent study investigating the PEAK3 interactome revealed that it acts as a dynamic scaffold together with essential adaptor proteins to regulate signal transduction ( Roy et al, 2023 ). Lipid raft environment has been shown to enhance LYN kinase activity ( Young et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…This structure includes a central SH2 domain flanked by two Src homologous 3 (SH3) domains on both sides [ 8 ]. The SH2 domain, spanning amino acids 60 to 152, is composed of 93 amino acids and enables GRB2 to recognize the phosphotyrosine consensus motif pYxNx (where Y is tyrosine, x represents any natural amino acid, and N is asparagine) in activated RTKs and other receptors [ 9 ]. On the other hand, there are two SH3 domains in GRB2, including a carboxyl-terminal SH3 (c-SH3) domain (residues 1–58) and an amino-terminal SH3 (n-SH3) domain (residues 156–215), both of which can interact with proline-rich motifs such as PxxP motifs (where P is proline), considered as a linker between the SH2 domain and downstream protein ( Figure 1 b,c) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%